Anticancer Effect and Apoptosis Induction of Gambogic Acid in Human Leukemia Cell Line K562 In Vitro - Chen, Jinhao (Med Sci Monit, 2015)
BACKGROUND: The aim of this study was to investigate the anticancer effect and related mechanisms of gambogic acid (GA), a traditional Chinese medicine, on human leukemia cell line K562, together with the effect on bone marrow mononuclear cells (MNCs). MATERIAL/METHODS: K562 cells and MNCs were treated with various concentrations and treatment times of GA. Inhibitory rate was detected by use of the Cell Counting Kit-8 (CCK-8) assay. Apoptosis was analyzed by morphological detection, Annexin-V/PI doubling staining, and TUNEL assays. The expression changes of pivotal proteins were evaluated by Western blotting. RESULTS: GA not only suppressed cell proliferation, but also induced apoptosis of K562 cells in a dose-dependent manner. While it did not significantly inhibit cell proliferation of MNCs, it did induce apoptosis in a dose-dependent manner. CCK-8 assay revealed that the proliferation of K562 cells was significantly inhibited when the concentration of GA was more than 0.5 μM. Morphological detection showed the nuclei became denser and more intense orange in K562 cells after GA treatment compared with the untreated group. The expression levels of BCL-2, nuclear factor-κB (NF-κB), c-myc, phosphatidylinositol3-kinase (PI3K), and phosphorylation of serine-threonine kinase (p-AKT) were down-regulated by GA. CONCLUSIONS: GA significantly suppressed the proliferation of K562 cells, but has less effect on MNCs. The inhibition of K562 cells proliferation and apoptosis induced by GA might be related to the down-regulation of BCL-2, NF-κB, c-myc, PI3K, and p-AKT.